Leverage as Intervening Variable of Profitability Post-pandemic (Covid-19) - ., Zulkifli; Saputra, Fendi; Zulkifli Muhammad, Mohd; Mareta, Sigit; Meiwanto Doktoralina, Caturida (KnE Social Sciences, 2023)
Cement companies in Indonesia support the government’s role in the development of the property sector. However, the Covid-19 pandemic has caused problems in making a profit. Therefore, the main problem of this study is to find out and analyze how profitability affects leverage and market value with the variables price earnings ratio (PER) and price to book value (PBV) as proxies. Second, knowing and analyzing leverage as an intervening variable that relates the effect of profitability to market value. This study uses the documentation analysis method of social research for exploring the theoretical model and empirical results of how profitability affects market value through leverage. The results from various empirical results showed that there is still little research on the ability of leverage as a variable to analyze cement companies listed on the Indonesia Stock Exchange. The results of the study can be expected to contribute to further research and facilitate the government to approach the development of cement companies to encourage the economy. Meanwhile, investors can be informed about the company’s financial performance. This study will provide advanced research guidance and convenience to the companies in providing solutions on how to increase market value by increasing profitability through leverage factors. Keywords: leverage, market value, profitability, Price Earnings Ratio (PER), Price to Book Value (PBV)